LAND DEGRADATION IN WESTERN KAZAKHSTAN (Journal of Geography and Environmental Management, 2026)
The study of land degradation and soil cover properties over the last few decades is one of the most important areas of research and has both scientific and applied character. This problem is especially relevant for Kazakhstan, a significant part of which is located in sub-arid and arid zones.  The main direct indicators of land degradation caused by the impact of increasing climate aridity and anthropogenic activity are external features of relief and vegetation cover of the earth surface, and exodynamic processes occurring on it, available for direct observation. The most pronounced processes of desertification and land destruction are observed in the territories of active hydrocarbon and mining development - Western and Central Kazakhstan. This paper presents the results of studies of land degradation and transformation (desertification) of the environment of the western region (Mangystau and Atyrau regions) of Kazakhstan for 2012-2024, conducted by the team of the Institute of Geography and Water Security of the Republic of Kazakhstan and the scientific team of the Faculty of Geography and Nature Management of KazNU named after Al-Farabi. The methodological basis of the work was route-field research, analysis of bibliographic and stock sources, cartographic analysis, social survey and graphical method.
Keywords: land degradation; desertification; soil cover; climatic changes; land use.